INTOXICATION PAR LE PEROXYDEDâ€™ HYDROGENE DESTINE A LA DECOLORATION DE CHEVEUX: DONNEES DU CENTRE ANTIPOISON ET DE PHARMACOVIGILANCE DU MAROC - Rajaa, Bellaje; Houda, Sefiani; Ben Ali, Doha; Abdelmajid, Soulaymani; Rachida, Soulaymani-Bencheikh; Abdelghani, Mokhtari (European Scientific Journal, ESJ, 2013)
To assess the extent and severity of poisoning by hydrogen peroxide dye hair used as the Moroccan population, a retrospective epidemiological study of all cases of poisoning reported, collected by the Moroccan poison control and pharmacovigilance center, between 1987 and 2011 was realized. The center has received 43 reports. The mean age was 18 Â± 2 years [0.1-50 years] and the female / male ratio was 2. The majority of cases of poisoning were occurred in th urban area (35 cases) and at home (31 cas). The digestive disorders were found in 17 cases, associeted or not with a neurological disorders (2 cases), cardiovascular disorders (1 case) and skin disorders e (1 case).Twenty patients were referred to the emergency care unit). A symptomatic treatment was ordered in 26 cases and gastrointestinal descontamination in 11 cases. The evolution was favorable in all cases.